A novel seawater and sea sand concrete-filled CFRP-carbon steel composite tube column: Seismic behavior and finite element analysis. (1st November 2022) - Zhang, Yirui; Wei, Yang; Li, Bing; Wang, Gaofei; Huang, Linjie
Highlights: Seismic tests of eight novel composite columns were conducted. Fiber reinforced polymer has an inhibitory effect on the steel tube buckling. A fiber model of the hysteretic behavior was investigated. A calculation method for the design-oriented drift capacity was proposed. Abstract: The seismic behavior of a novel seawater and sea sand concrete (SSC)-filled carbon fiber-reinforced polymer (CFRP)-carbon steel composite tube (SFSCT) column under combined axial compression and reversed cyclic loadings was studied in this paper. This structure makes use of seawater and sea sand resources, and CFRP was adopted to isolate the corrosion by chloride ions on the steel tube. Tests of eight composite columns were carried out. The test parameters include the axial compression ratio, the number of CFRP layers and the bonding direction. The test results revealed that all of the specimens displayed superb seismic performance with a drift ratio over 4%. The failure of the SFSCT column exhibits a typical compressive-flexural failure mode. Compared with the results of the SSC-filled steel tube columns, the hoop strain of the specimen under additional CFRP confinement is reduced by 1.6 times, and the flexural strength and drift capacity increase by 22% and 17%, respectively. A fiber model was created by finite element analysis, and parametric studies of the main design parameters were performed. The effects of the steel tube and CFRP on the seismic performance were evaluated. Using experiments and finite element analysis, the relationships among the drift capacity, axial compression ratio and confinement level were investigated. A design method for predicting the drift capacity of SFSCT columns was proposed.